IFITIRĀḌĪ MAHMUD YUNUS’S INTERPRETATION OF THE PHENOMENON OF FASTING AT THE POLES IN SURAH AL-BAQARAH: 183—185 - Salsabila, Laily; Hasan, Moh. Abdul Kholiq (Tanzil: Jurnal Studi Al-Quran, 2024)
This study focused on the reinterpretation of Mahmud Yunus’ thoughts in contextualizing Surah Al-Baqarah [2]:183—185 for Muslim communities in the polar regions. The formulation of the problem arises, what was the form of Yunus’ ifitirāḍī interpretation of the phenomenon of fasting at the Pole in surah Al-Baqarah 183—185? What factors shape Mahmud Yunus’ ifitirāḍī interpretation of the phenomenon of fasting at the Pole in Surah Al-Baqarah 183—185? Based on qualitative data and Gadamer’s hermeneutical analysis theory, this article shows Mahmud Yunus’ interpretation of Surah Al-Baqarah [2]: 183—185 in five models. First, Yunus’ thoughts prioritize the rational and contextual side in understanding the fasting verse in Al-Baqarah [2]: 183—185 which is inspired by ‘Abduh’s thoughts. Second, Mahmud Yunus firmly stated that there is no obligation to fast in the Polar region because the sunrise and sunset cannot be seen. Third, Mahmud Yunus offers an interpretation of ifitirāḍī by continuing to fast through information about the new moon from countries around Mecca or nearby countries. Fourth, the option of not fasting at the Pole can be replaced by giving fiḍyah in another place that has a larger population than the population in the Polar region. This research was expected to provide important information regarding rethinking the contextual interpretation offered by Mahmud Yunus in understanding the fasting verses logically and through two alternative interpretations of ifitirāḍī fasting verses in the Polar region with Mahmud Yunus’s distinctive futuristic style, it is hoped that it will be able to provide solutions and answers regarding the suitability of the Qur’an in the present and future in a solution, rational, and contextual manner.